Beyond pristine biochar: A comparative study on environmental sustainability and tetracycline adsorption performance of pristine, activated, and iron-nitrogen co-doped hardwood waste-derived biochar - Subhash Chandra; Isha Medha; Chandra Sekhar Tiwary; Nabisab Mujawar Mubarak (Biomass and Bioenergy, 2027)

Hepatotoxicity of anti-tuberculosis therapy and the hepatoprotective effect of traditional medicine - Damini C.; Anuj Nautiyal; Bharat Joshi; Vishu Kumar; Dev Singh Jangpangi; Subhash Chandra; Samir Bhargava; Bhavna Kumar; Henrique D.M. Coutinho; Gorika Tomar (Food and Humanity, 2026)

Hydrobiological drivers of zooplankton community structure and seasonal succession in a hypersaline endorheic ecosystem - Pankaj Yadav; Kanchan Singhvi; Dinesh Kumar Saini; Anima Sharma; Subhash Chandra (Wetlands Ecology and Management, 2026)

Optimizing Sugarcane Yield Through Seasonal Planting Strategies: A Field Study in Sub-Tropical Conditions - Priyanka Singh; Subhash Chandra Singh; Prasoon Kumar; Manmohan Singh (Sugar Tech, 2026)

A Robust Hybrid Deep Learning Model for GHI Forecasting Incorporating EEMD, CSA Optimization, and Transformer–GRU Networks - Girijapati Sharma; Subhash Chandra; Arvind Kumar Yadav (Pure and Applied Geophysics, 2026)

A Rapid and Sensitive Loop-Mediated Isothermal Amplification (LAMP) Diagnostic Assay for Globodera rostochiensis - Aarti Bairwa; Bhawna Dipta; Pavan Kalyan P.; Neha Sharma; Subhash Shivaramu; Kailash Chandra Naga; Priyank Hanuman Mhatre; Sanjeev Sharma; Brajesh Singh (American Journal of Potato Research, 2026)

Harnessing plant-derived bioactive compounds as LOX-1 inhibitors in Helicobacter pylori-driven gastric inflammation - Nfor Gael Njini; Siddharth Singh; Harshita Shrivastava; Divyasree Vulli; Sakshi Subhash Kale; Lauve Rachel Tchokouaha Yamthe; Cedric Tchinda Fossi; Vasundhra Bhandari; Hem Chandra Jha (Toxicology and Applied Pharmacology, 2026)

Viscoelastic Deformation Analysis of a Non-planar Strike-Slip Fault in Standard Linear Solid - Tanushree Biswas; Seema Sarkar Mondal; Subhash Chandra Mondal (Pure and Applied Geophysics, 2026)

Application of machine learning tools for prediction of seed cotton yield in upland cotton (G. hirsutum L.) under irrigated ecosystem - Debashis Paul; Vinita Gotmare; M. Saravanan; Sandeep Bagri; Harish Kumbhalkar; Subhash Chandra; S. K. Verma; Rishi Kumar; Y. G. Prasad (Euphytica, 2026)

Mitigating the Environmental Impacts of the Sugarcane Industry in India: A Review of Best Management Practices - Shreya Kotnala; Arunima Nayak; Brij Bhushan; Shalini Tiwari; Ajay Kumar; Mohd Amin Mir; Subhash Chandra (Sugar Tech, 2026)

Deformation due to non-planar fault movement in fractional Maxwell medium - Pabita Mahato; Seema Sarkar Mondal; Subhash Chandra Mondal (Acta Geophysica, 2026)

An investigation of the effects of Static Coulomb stress variations of four thrust earthquakes on subsequent events - Ankush Kumar Ruhela; Josodhir Das; Subhash Chandra Gupta; Ram Bichar Singh Yadav (Arabian Journal of Geosciences, 2026)

Probing the influence of low-level laser therapy on cellular and standard proteins by light emitting diode -induced autofluorescence spectroscopy - Shanmukha Sreeya Devarakonda; Shaik Basha; Ameera K; Anshuman Mishra; Subhash Chandra; Krishna Kishore Mahato (Journal of Photochemistry and Photobiology B: Biology, 2026)

GC-MS analysis, phytochemical profiling and pharmacological assessment of Abies pindrow from Uttarakhand - Sarla Saklani; Monika Kawra; Subhash Chandra; Sakshi; Henrique Douglas Melo Coutinho (Food and Humanity, 2025)

Articulating the multifaceted application of bioactive compound decorated silver/gold nanoparticles: Current and future prospective - Pooja V. Nagime; Vaishali S. Chandak; Shreya Kotnala; Mukesh Pandey; Titilope John Jayeoye; Sheeba Shafi; Subhash Chandra; Shradhanjali Singh; Vijay R. Chidrawar; Sudarshan Singh (Biocatalysis and Agricultural Biotechnology, 2025)

Unraveling the interplay between RAS axes and NOX signaling in fibroblasts during cardiac fibrosis - Gauri Chaturvedi; Anita Chauhan; Nandini Dubey; Sandeep Seth; Jagriti Bhatia; Subhash Chandra Yadav; Harlokesh Narayan Yadav (Molecular and Cellular Biochemistry, 2025)

Evaluation of antibacterial potential of Terminalia arjuna aqueous extract against Xanthomonas oryzae and deciphering its mechanism by computational methods - Tushar Joshi; Disha Tewari; Satish Chandra Pandey; Manish Tripathi; Priyanka Maiti; Shalini Mathpal; Priyanka Sharma; Mukesh Samant; Subhash Chandra (European Journal of Plant Pathology, 2025)

Enhancing solar radiation forecasting accuracy with a hybrid SA-Bi-LSTM-Bi-GRU model - Girijapati Sharma; Subhash Chandra; Arvind Kumar Yadav; Rahul Gupta (Earth Science Informatics, 2025)

Impact of heavy metal toxicity on the human health and environment - Shreya Kotnala; Shalini Tiwari; Arunima Nayak; Brij Bhushan; Subhash Chandra; Cassio Rocha Medeiros; Henrique Douglas Melo Coutinho (Science of The Total Environment, 2025)

Antibacterial Activity, Phytochemical Analysis of C. coggygria Leaf Extracts Against S. typhi, and Computational Studies to Screen Potential Drug Candidates - Ankit Negi; Pooja Pant; Shalini Mathpal; Disha Tewari; Santosh Kumar Upadhyay; Subhash Chandra; Rishendra Kumar (Indian Journal of Microbiology, 2025)

Quantitative Analysis on Expression of Insecticidal Crystal Proteins in Different Plant Parts of BG-II Cotton Hybrids at Various Phenological Stages - Debashis Paul; Rishi Kumar; G. Balasubhramani; Sandeep Bagri; Subhash Chandra; S. Manickam; Satpal Singh; A. H. Prakash; Y. G. Prasad (Agricultural Research, 2025)

Investigating the aging-modulatory mechanism of Rasayana Churna, an Ayurvedic herbal formulation, using a computational approach - Amisha Bisht; Anita Nayal; Disha Tewari; Sanjay Kumar; Subhash Chandra (Biogerontology, 2025)

Ultrahigh-performance NiWO4 nanoparticles anchored ZnO nanoflakes as a potential electrode for energy storage applications - Yanli Xu; Waqed H. Hassan; Mohamed R. El-Sharkawy; Subhash Chandra; Ashish Verma; Mohammed Al-Bahrani; Shaik Mohammad Irshad; Saiful Islam; Ibrahim Mahariq (Fuel, 2025)

Pink Bollworm, Pectinophora gossypiella (Saunders) Infestation Escalates from Incipient to Serious Proportions in North Cotton Zone of India - Rishi Kumar; Debashis Paul; S. K. Sain; Amarpreet Singh; Subhash Chandra; Satpal Singh; Rupinder Singh Cheema; Y. G. Prasad (Journal of Crop Health, 2025)

Influence of Bemisia tabaci-Induced Plant Volatiles on the Host-Choice Behavior of Tuta absoluta - Subhash Shivaramu; Kamala Jayanthi Pagadala Damodaram; Anuj Bhatnagar; Kailash Chandra Naga; Varun Yennurukadirenahalli Byregowda; Aarti Bairwa; Sanjeev Sharma; Rajesh Kumar Singh; Brajesh Singh; Vivek Kempraj (Journal of Chemical Ecology, 2025)

Measurement of natural radionuclides and health risk assessment in soil samples of the Main Central Thrust region in Garhwal Himalaya, India - Krishna Pal Singh; Subhash Chandra; Mukesh Prasad; Pooja Panwar; Abhishek Joshi; Shubham Sharma; Sanjeev Kimothi; Ganesh Prasad; Rohit Mehra; R. C. Ramola (Environmental Monitoring and Assessment, 2025)

Flupyradifurone application: A promising approach to curtail tomato leaf curl New Delhi virus (ToLCNDV) transmission vectored by Bemisia tabaci in potato farming - Nitish Modgill; Kailash Chandra Naga; Dnyaneshwar Madhukar Firake; Rahul Kumar Tiwari; Subhash Shivaramu; Ravinder Kumar; Anuj Bhatnagar; Tanuja Buckseth; Aarti Bairwa; Chandan Maharana; Sanjeev Sharma; Brajesh Singh (Crop Protection, 2025)

Estimation of source parameters of local earthquakes near Koldam, Himachal Himalaya, India - Ankush Kumar Ruhela; Subhash Chandra Gupta; Josodhir Das (Arabian Journal of Geosciences, 2025)

Presence of emerging organic contaminants and microbial indicators in surface water and groundwater in urban India - Bentje Brauns; Subhash Chandra; Wayne Civil; Dan J. Lapworth; Alan M. MacDonald; Andrew A. McKenzie; Daniel S. Read; Muddu Sekhar; Andrew C. Singer; Amritha Thankachan; Holly J. Tipper (Environmental Pollution, 2024)

Efficacy of Nigella sativa seed oil against psychophysical stress induced irritable bowel syndrome and anxiety-like symptoms in Wistar rats - Madhu Sharma; Swati Rana; Shiwangi Aggarwal; Aitizaz Ul Ahsan; Muskan Budhwar; Sweety Mehra; Subhash Chandra Sahoo; Mani Chopra (Psychopharmacology, 2024)

Correction: Synthesis, characterization, and practical applications of perovskite quantum dots: recent update - Subhash Chandra; Mohammed Ahmed Mustafa; Kamil Ghadir; Pooja Bansal; Mahamedha Deorari; Dheyaa Yahaia Alhameedi; Mahmood Hasen shuhata Alubiady; Ahmed Muzahem Al-Ani; Safia Obaidur Rab; Sally Salih Jumaa; Munther Kadhim Abosaoda (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Synthesis, characterization, and practical applications of perovskite quantum dots: recent update - Subhash Chandra; Mohammed Ahmed Mustafa; Kamil Ghadir; Pooja Bansal; Mahamedha Deorari; Dheyaa Yahaia Alhameedi; Mahmood Hasen shuhata Alubiady; Ahmed Muzahem Al-Ani; Safia Obaidur Rab; Sally Salih Jumaa; Munther Kadhim Abosaoda (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Synthesis, Properties, and Mechanistic Release-Kinetics Modeling of Biochar-Based Slow-Release Nitrogen Fertilizers and Their Field Efficacy - Prayasi Nayak; Tony Manoj K. Nandipamu; Sumit Chaturvedi; V. C. Dhyani; Subhash Chandra (Journal of Soil Science and Plant Nutrition, 2024)

Rapid transfer of the leaf rust resistance gene Lr52 for the improvement of bread wheat cultivar HD3086 - Naman Raj; Hariom Shukla; Priyanka Agarwal; Ajay Kumar Chandra; Ramesh Bhurta; Subhash Bijarania; Manish Kumar Choudhary; Raghunandan K; Niharika Mallick; Niranjana M; Arun Kumar M. B; Lekshmy Sathee; et al. (Physiological and Molecular Plant Pathology, 2024)

Soil carbon sequestration potential of different land use systems: evidence from sub-humid southern plains and Aravalli hills of Rajasthan, India - Ram Bhawan Meena; Subhash Chander Meena; Avinash Chandra Rathore; Dinesh Chand Meena; Roshan Lal Meena; Nurnabi Meherul Alam; Kamal Kishor Sharma; Prabhat Kumar; Gopal Lal Meena; Murli Dhar Meena (Environmental Monitoring and Assessment, 2024)

Network pharmacology-based approach to investigate the molecular targets and molecular mechanisms of Rosmarinus officinalis L. for treating aging-related disorders - Amisha Bisht; Disha Tewari; Sanjay Kumar; Subhash Chandra (Biogerontology, 2024)

Exploring the molecular mechanism of anti-inflammatory action of Coriandrum sativum using network pharmacology, molecular dynamic simulation, and density functional theory - Shilpi Rawat; Pankaja Pandey; Priyanka Joshi; Amisha Bisht; Vijay Arya; Priyanka Maiti; Subhash Chandra (Journal of Proteins and Proteomics, 2024)

Identification of hub genes associated with stripe rust disease in wheat through integrative transcriptome and gene-based association study - Divya Chauhan; Dwijesh Chandra Mishra; Shikha Mittal; Sushma Rani; Jyotika Bhati; Sundeep Kumar; Subhash C. Bhardwaj; Monendra Grover; Neeraj Budhlakoti; Suphiya Khan (South African Journal of Botany, 2024)

Repurposing of Drug Bank Compounds against Plasmodium falciparum Dihydroorotate Dehydrogenase as novel anti malarial drug candidates by Computational approaches - Priyanka Joshi; Pankaja Pandey; Shilpi Rawat; Subhash Chandra (In Silico Pharmacology, 2024)

Network pharmacology, molecular docking, and molecular dynamics simulation to elucidate the mechanism of anti-aging action of Tinospora cordifolia - Amisha Bisht; Disha Tewari; Sanjay Kumar; Subhash Chandra (Molecular Diversity, 2024)

Microbiological acceptance criteria, specifications of herbal drugs and herbal drug preparations in various pharmacopoeias: a global scenario - Ramesh Munukuntla; Akhilesh Tiwari; Ravi Shankar Yadav; A. Jayanthy; Subhash Chandra Verma; Raman Mohan Singh (DARU Journal of Pharmaceutical Sciences, 2024)

Identification of alpha-glucosidase enzyme inhibitors from phytochemicals via integrated deep learning, molecular docking, molecular dynamics simulation, and MMPBSA analysis - Priyanka Sharma; Vishal Sharma; Shalini Mathpal; Disha Tewari; Subhash Chandra; Sushma Tamta (South African Journal of Botany, 2024)

Enhancing Wheat Productivity Through Genotypes and Growth Regulators Application Under Higher Fertility Conditions in Sub-humid Climate - Rajender Singh Chhokar; Neeraj Kumar; Subhash Chander Gill; Subhash Chandra Tripathi; Gyanendra Singh (International Journal of Plant Production, 2024)

Role of reactive oxygen species and antioxidative enzymes in the loss and re-establishment of desiccation tolerance in germinated pea seeds - Balram Sahu; Subhash Chandra Naithani (South African Journal of Botany, 2023)

Measurement of radon concentration in soil gas and radon exhalation rate from soil samples along and across the Main Central Thrust of Garhwal Himalaya, India - Krishna Pal Singh; Subhash Chandra; Pooja Panwar; Abhishek Joshi; Ganesh Prasad; G. S. Gusain; R. C. Ramola (Environmental Geochemistry and Health, 2023)

Overexpression of flowering locus D (FLD) in Indian mustard (Brassica juncea) enhances tolerance to Alternaria brassicae and Sclerotinia sclerotiorum - Shashi Shekhar; Ruby Panwar; Subhash Chandra Prasad; Deepak Kumar; Anjana Rustagi (Plant Cell Reports, 2023)

Effect of ZSB with Graded Levels of Zinc Fertilizer on Yield and Zinc Uptake Under Maize Cultivation - Deepa Verma; Ram Hari Meena; Aradhana Sukhwal; Gajanand Jat; Subhash Chandra Meena; Sudhir K. Upadhyay; Devendra Jain (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2023)

Development of Rice Straw-derived Biochar-Bentonite Composite and its Application for in situ Sequestration of Ammonium and Phosphate Ions in the Degraded Mine Soil - Isha Medha; Subhash Chandra; Jayanta Bhattacharya; Biswajit Samal; Kumar Raja Vanapalli (Environmental Management, 2023)

Fatty acids analysis, antioxidant, antimicrobial and biological activity of essential oil of Skimmia laureola Leaves - V. K. Bisht; A. K. Bhandari; L. S. Kandari; T. Negi; Subhash Chandra; Sarla Saklani; Santwana Palai; Bruna Caroline Gonçalves Vasconcelo de Lacerda; Henrique D. M. Coutinho (Vegetos, 2023)

Identification of Wheat Genotypes Resilient to Terminal Heat Stress Using GGE Biplot Analysis - Kiran Devi; Sulekha Chahal; Karnam Venkatesh; Surendra Singh; Subhash Chandra Tripathi; H. M. Mamrutha; Ruchika Sharma; Sonia Sheoran; Nagendra Kumar Singh; Gyanendra Singh; Gyanendra Pratap Singh; Ratan Tiwari (Journal of Soil Science and Plant Nutrition, 2022)

Computational investigation of drug bank compounds against 3C-like protease (3CLpro) of SARS-CoV-2 using deep learning and molecular dynamics simulation - Tushar Joshi; Priyanka Sharma; Shalini Mathpal; Tanuja Joshi; Priyanka Maiti; Mahesha Nand; Veena Pande; Subhash Chandra (Molecular Diversity, 2022)

Nickel-mediated lead dynamics and their interactive effect on lead partitioning and phytoremediation indices in spinach - Mohan Lal Dotaniya; Jaypal Singh Pipalde; Ramesh Chandra Jain; Rajendiran Selladurai; Subhash Chandra Gupta; Madhav Das Vyas; M Vassanda Coumar; Sonalika Sahoo; Jayanta Kumar Saha; Ajay Kumar (Environmental Monitoring and Assessment, 2022)

Use of Petroleum-Derived Spray Oils for the Management of Vector-Virus Complex in Potato - Mohd Abas Shah; Kailash Chandra Naga; Shivaramu Subhash; Sanjeev Sharma; Raj Kumar (Potato Research, 2022)

Determination of characteristics of the microearthquakes occurring in Lesser and Higher Himalaya India - Neetu Goswami; Subhash Chandra Gupta (Acta Geophysica, 2022)

Seed longevity studies in wild type, cultivated and inter-specific recombinant inbred lines (RILs) of soybean [Glycine max (L.) Merr.] - Subhash Chandra; Akshay Talukdar; Yashpal Taak; Raju R. Yadav; Manisha Saini; N. S. Sipani (Genetic Resources and Crop Evolution, 2022)

Roles of Nitric Oxide in Conferring Multiple Abiotic Stress Tolerance in Plants and Crosstalk with Other Plant Growth Regulators - Rajesh Kumar Singhal; Hanuman Singh Jatav; Tariq Aftab; Saurabh Pandey; Udit Nandan Mishra; Jyoti Chauhan; Subhash Chand; Indu; Debanjana Saha; Basant Kumar Dadarwal; Kailash Chandra; Mudasser Ahmed Khan; et al. (Journal of Plant Growth Regulation, 2021)

Stress and development phenotyping of Hsp101 and diverse other Hsp mutants of Arabidopsis thaliana - Lalit Dev Tiwari; Ritesh Kumar; Vijyesh Sharma; Alok Kumar Sahu; Balram Sahu; Subhash Chandra Naithani; Anil Grover (Journal of Plant Biochemistry and Biotechnology, 2021)

Study on nutritional and phytochemical profile of seven edible food supplements of Uttarakhand (Garhwal Himalaya) - Subhash Chandra; Sarla Saklani; Abhishek Mathur (Vegetos, 2021)

Using Chou’s 5-steps rule to study pharmacophore-based virtual screening of SARS-CoV-2 Mpro inhibitors - Hemlata Pundir; Tanuja Joshi; Tushar Joshi; Priyanka Sharma; Shalini Mathpal; Subhash Chandra; Sushma Tamta (Molecular Diversity, 2021)

Structure-based screening of novel lichen compounds against SARS Coronavirus main protease (Mpro) as potentials inhibitors of COVID-19 - Tanuja Joshi; Priyanka Sharma; Tushar Joshi; Hemlata Pundir; Shalini Mathpal; Subhash Chandra (Molecular Diversity, 2021)

Novel role of photoinsensitive alleles in adaptation of soybean [Glycine max (L.) Merr.] to rainfed short growing seasons of lower latitudes - Rachana Tripathi; Nisha Agrawal; Giriraj Kumawat; Sanjay Gupta; Mrinal Kuchlan; Shivakumar Maranna; Vennampally Nataraj; Punam Kuchlan; Gyanesh K. Satpute; Milind B. Ratnaparkhe; Vangala Rajesh; Subhash Chandra; et al. (Genetic Resources and Crop Evolution, 2021)

Identification of novel genetic sources for agronomic and quality traits in soybean using multi-trait allele specific genic marker assays - Giriraj Kumawat; Shivakumar Maranna; Sanjay Gupta; Rachana Tripathi; Nisha Agrawal; Vijayata Singh; Vangala Rajesh; Subhash Chandra; Viraj Kamble; Vennampally Nataraj; Abhishek Bharti; Mahaveer P. Sharma; et al. (Journal of Plant Biochemistry and Biotechnology, 2021)

Conservation of gene architecture and domains amidst sequence divergence in the hsrω lncRNA gene across the Drosophila genus: an in silico analysis - Ranjan Kumar Sahu; Eshita Mutt; Subhash Chandra Lakhotia (Journal of Genetics, 2020)

Genetics and mapping of seed coat impermeability in soybean using inter-specific populations - Subhash Chandra; Yashpal Taak; Darasing Ramsing Rathod; Raju Ratan Yadav; Shatakshi Poonia; V. Sreenivasa; Akshay Talukdar (Physiology and Molecular Biology of Plants, 2020)

Spatial mapping and modeling of arsenic contamination of groundwater and risk assessment through geospatial interpolation technique - Merina Ghosh; Dilip Kumar Pal; Subhash Chandra Santra (Environment, Development and Sustainability, 2020)

Foliar Application of Iron Fortified Bacteriosiderophore Improves Growth and Grain Fe Concentration in Wheat and Soybean - Sandeep Sharma; Subhash Chandra; Arun Kumar; Prem Bindraban; Anil Kumar Saxena; Veena Pande; Renu Pandey (Indian Journal of Microbiology, 2019)

Impact of dust storm on phytoplankton bloom over the Arabian Sea: a case study during March 2012 - Kunal Bali; Amit Kumar Mishra; Sachchidanand Singh; Subhash Chandra; Yoav Lehahn (Environmental Science and Pollution Research, 2019)

Foliar application of organic and inorganic iron formulation induces differential detoxification response to improve growth and biofortification in soybean - Sandeep Sharma; Hina Malhotra; Priyanka Borah; Mukesh Kumar Meena; Prem Bindraban; Subhash Chandra; Veena Pande; Renu Pandey (Plant Physiology Reports, 2019)

Community dynamics and functional characteristics of naphthalene‐degrading populations in contaminated surface sediments and hypoxic/anoxic groundwater - Roland C. Wilhelm; Buck T. Hanson; Subhash Chandra; Eugene Madsen (Environmental Microbiology, 2018)
Summary Earlier research on the biogeochemical factors affecting natural attenuation in coal‐tar contaminated groundwater, at South Glens Falls, NY, revealed the importance of anaerobic metabolism and trophic interactions between degrader and bacterivore populations. Field‐based characterizations of both phenomena have proven challenging, but advances in stable isotope probing (SIP), single‐cell imaging and shotgun metagenomics now provide cultivation‐independent tools for their study. We tracked carbon from 13 C‐labelled naphthalene through microbial populations in contaminated surface sediments over 6 days using respiration assays, secondary ion mass spectrometry imaging and shotgun metagenomics to disentangle the contaminant‐based trophic web. Contaminant‐exposed communities in hypoxic/anoxic groundwater were contrasted with those from oxic surface sediments to identify putative features of anaerobic catabolism of naphthalene. In total, six bacteria were responsible for naphthalene degradation. Cupriavidus , Ralstonia and Sphingomonas predominated at the earliest stages of SIP incubations and were succeeded in later stages by Stenotrophomonas and Rhodococcus. Metagenome‐assembled genomes provided evidence for the ecological and functional characteristics underlying these temporal shifts. Identical species of Stenotrophomonas and Rhodococcus were abundant in the most contaminated, anoxic groundwater. Apparent increases in bacterivorous protozoa were observed following exposure to naphthalene, though insignificant amounts of carbon were transferred between bacterial degraders and populations of secondary feeders.

High Performance Thin Layer Chromatography Fingerprint Profile of Rhizome Extracts of Five Important Curcuma Species - Sachin Subhash Kharade; Kailash Chandra Samal; Gyana Ranjan Rout (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Agronomic fortification of rice grains with secondary and micronutrients under differing crop management and soil moisture regimes in the north Indian Plains - Anchal Dass; Subhash Chandra; Norman Uphoff; Anil K. Choudhary; Ranjan Bhattacharyya; K. S. Rana (Paddy and Water Environment, 2017)

A Study on Gene Expression Profile of Endogenous Antioxidant Enzymes: CAT, MnSOD and GPx in Dengue Patients - Cleetus Cherupanakkal; Vijayakumar Ramachadrappa; Tamilarasu Kadhiravan; Narayanan Parameswaran; Subhash Chandra Parija; Agieshkumar Balakrishna Pillai; Soundravally Rajendiran (Indian Journal of Clinical Biochemistry, 2017)

Active oxygen species metabolism in neem (Azadirachta indica) seeds exposed to natural ageing and controlled deterioration - Alok Kumar Sahu; Balram Sahu; Avinash Soni; Subhash Chandra Naithani (Acta Physiologiae Plantarum, 2017)

Differential expression of NADPH oxidase-2 (Nox-2) and nuclear factor-erythroid 2-related factor 2 (Nrf2) transcripts in peripheral blood mononuclear cells isolated from dengue patients - Cleetus Cherupanakkal; Vijayakumar Ramachadrappa; Tamilarasu Kadhiravan; Narayanan Parameswaran; Subhash Chandra Parija; Agieshkumar Balakrishna Pillai; Soundravally Rajendiran (VirusDisease, 2017)

Dose-dependent response of Trichoderma harzianum in improving drought tolerance in rice genotypes - Veena Pandey; Mohammad W. Ansari; Suresh Tula; Sandep Yadav; Ranjan K. Sahoo; Nandini Shukla; Gurdeep Bains; Shail Badal; Subhash Chandra; A. K. Gaur; Atul Kumar; Alok Shukla; et al. (Planta, 2016)

Arsenic contamination of groundwater and its induced health effects in Shahpur block, Bhojpur district, Bihar state, India: risk evaluation - Dipankar Chakraborti; Mohammad Mahmudur Rahman; Sad Ahamed; Rathindra Nath Dutta; Shyamapada Pati; Subhash Chandra Mukherjee (Environmental Science and Pollution Research, 2016)

Effect of Extended Water Stress on Growth, Tiller Mortality and Nutrient Recovery Under System of Rice Intensification - K. K. Hazra; Subhash Chandra (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Influence of field re-ponding pattern and plant spacing on rice root–shoot characteristics, yield, and water productivity of two modern cultivars under SRI management in Indian Mollisols - Anchal Dass; Subhash Chandra; Anil K. Choudhary; Gurvinder Singh; S. Sudhishri (Paddy and Water Environment, 2016)

Spectroscopic and Quantum Mechanical Approach of Solvatochromic Immobilization: Modulation of Electronic Structure and Excited-State Properties of 1,8-Naphthalimide Derivative - Soumya Sundar Mati; Sayantani Chall; Soumyadipta Rakshit; Subhash Chandra Bhattacharya (Journal of Fluorescence, 2015)

Efficiency of ISSR and RAPD markers in genetic divergence analysis and conservation management of Justicia adhatoda L., a medicinal plant - Amit Kumar; Priyanka Mishra; Subhash Chandra Singh; Velusamy Sundaresan (Plant Systematics and Evolution, 2014)

Mild to prolonged stress increased rice tillering and source-to-sink nutrient translocation under SRI management - K. K. Hazra; Subhash Chandra (Paddy and Water Environment, 2014)

New natural compounds from Rhododendron lepidotum - Shakeel-u-Rehman; Shahnawaz Nabi Sofi; Mohammad Akbar Khuroo; Subhash Chandra Taneja; Khursheed Ahmad Bhat; Ram Vishwakarma (Natural Product Research, 2013)

In vitro propagation, genetic and secondary metabolite analysis of Aconitum violaceum Jacq.: a threatened medicinal herb - Janhvi Mishra Rawat; Balwant Rawat; Rajneesh K. Agnihotri; Anup Chandra; Subhash Nautiyal (Acta Physiologiae Plantarum, 2013)

ISSR and RAPD based evaluation of genetic fidelity and active ingredient analysis of regenerated plants of Picrorhiza kurroa - Janhvi Mishra Rawat; Balwant Rawat; Shakti Mehrotra; Anup Chandra; Subhash Nautiyal (Acta Physiologiae Plantarum, 2013)

Isoiridomyrmecin rich essential oil from Nepeta erecta Benth. and its antioxidant activity - Dinesh S. Bisht; Subhash C. Joshi; Rajendra C. Padalia; Chandra S. Mathela (Natural Product Research, 2012)

Synthesis and biological evaluation of 2-amino-5-sulfanyl-1,3,4-thiadiazole derivatives as antidepressant, anxiolytics and anticonvulsant agents - Rajesh Sharma; Ganesh Prasad Misra; Jitendra Sainy; Subhash Chandra Chaturvedi (Medicinal Chemistry Research, 2011)

Deglycosylated milin unfolds via inactive monomeric intermediates - Subhash Chandra Yadav; N. K. Prasanna Kumari; Medicherla V. Jagannadham (European Biophysics Journal, 2010)

Equilibrium unfolding of kinetically stable serine protease milin: the presence of various active and inactive dimeric intermediates - Subhash Chandra Yadav; Medicherla V. Jagannadham; Suman Kundu (European Biophysics Journal, 2010)

Complete conformational stability of kinetically stable dimeric serine protease milin against pH, temperature, urea, and proteolysis - Subhash Chandra Yadav; Medicherla V. Jagannadham (European Biophysics Journal, 2009)

Dynamic secondary ion mass spectrometry imaging of microbial populations utilizing 13 C‐labelled substrates in pure culture and in soil - Graham M. Pumphrey; Buck T. Hanson; Subhash Chandra; Eugene L. Madsen (Environmental Microbiology, 2009)
Summary We demonstrate that dynamic secondary ion mass spectrometry (SIMS)‐based ion microscopy can provide a means of measuring 13 C assimilation into individual bacterial cells grown on 13 C‐labelled organic compounds in the laboratory and in field soil. We grew pure cultures of Pseudomonas putida NCIB 9816‐4 in minimal media with known mixtures of 12 C‐ and 13 C‐glucose and analysed individual cells via SIMS imaging. Individual cells yielded signals of masses 12, 13, 24, 25, 26 and 27 as negative secondary ions indicating the presence of 12 C – , 13 C – , 24 ( 12 C 2 ) – , 25 ( 12 C 13 C) – , 26 ( 12 C 14 N) – and 27 ( 13 C 14 N) – ions respectively. We verified that ratios of signals taken from the same cells only changed minimally during a ∼4.5 min period of primary O 2 + beam sputtering by the dynamic SIMS instrument in microscope detection mode. There was a clear relationship between mass 27 and mass 26 signals in Psuedomonas putida cells grown in media containing varying proportions of 12 C‐ to 13 C‐glucose: a standard curve was generated to predict 13 C‐enrichment in unknown samples. We then used two strains of Pseudomonas putida able to grow on either all or only a part of a mixture of 13 C‐labelled and unlabelled carbon sources to verify that differential 13 C signals measured by SIMS were due to 13 C assimilation into cell biomass. Finally, we made three key observations after applying SIMS ion microscopy to soil samples from a field experiment receiving 12 C‐ or 13 C‐phenol: (i) cells enriched in 13 C were heterogeneously distributed among soil populations; (ii) 13 C‐labelled cells were detected in soil that was dosed a single time with 13 C‐phenol; and (iii) in soil that received 12 doses of 13 C‐phenol, 27% of the cells in the total community were more than 90% 13 C‐labelled.

Correlation between serum lipid profile and carotid intima-media thickness in Polycystic Ovarian Syndrome - Sarama Saha; Chandan Sarkar; Subhash Chandra Biswas; R. Karim (Indian Journal of Clinical Biochemistry, 2008)

α-Glucosidase inhibitory activity and in vitro antioxidant activities of alcohol-water extract (AWE) of Ichnocarpus frutescens leaves - Chidambaram Kumarappan; Subhash Chandra Mandal (Medicinal Chemistry Research, 2008)

Oxygenated chalcones and bischalcones as a new class of inhibitors of DNA topoisomerase II of malarial parasites - Shalini Srivastava; Shweta Joshi; Alok R. Singh; Sarika Yadav; A. S. Saxena; V. J. Ram; Subhash Chandra; J. K. Saxena (Medicinal Chemistry Research, 2008)

A triterpenediol from Boswellia serrata induces apoptosis through both the intrinsic and extrinsic apoptotic pathways in human leukemia HL-60 cells - Shashi Bhushan; Ajay Kumar; Fayaz Malik; Samar Singh Andotra; Vijay Kumar Sethi; Indu Pal Kaur; Subhash Chandra Taneja; Ghulam Nabi Qazi; Jaswant Singh (Apoptosis, 2007)

The pattern of genetic diversity of Guinea-race Sorghum bicolor (L.) Moench landraces as revealed with SSR markers - Rolf T. Folkertsma; H. Frederick W. Rattunde; Subhash Chandra; G. Soma Raju; C. Tom Hash (Theoretical and Applied Genetics, 2005)

Kuth (Saussurea lappa) cultivation in the cold desert environment of the Lahaul valley, northwestern Himalaya, India: arising threats and need to revive socio-economic values - Chandra P. Kuniyal; Yashwant S. Rawat; Santaram S. Oinam; Jagdish C. Kuniyal; Subhash C. R. Vishvakarma (Biodiversity and Conservation, 2005)

Inhibition of Biosynthesis and Activity of Nitrogenase in Azospirillum brasilense Sp7 Under Salinity Stress - Anil Kumar Tripathi; Thirunavukkarasu Nagarajan; Subhash Chandra Verma; Daniel Le Rudulier (Current Microbiology, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Enzymatic discoloration and phenolic content of potato tubers from cultivars resistant and susceptible to the golden nematode - Nell I. Mondy; Subhash Chandra; William D. Evans (American Journal of Potato Research, 1985)

The effect of phosphorus fertilization on the chemical quality of Katahdin potatoes - Lisa B. Klein; Subhash Chandra; N. I. Mondy (American Journal of Potato Research, 1980)

Ultrastructure of potato tubers infected with potato virus X - N. I. Mondy; Subhash Chandra; M. A. Cukierski (American Journal of Potato Research, 1980)

Quality of potato tubers as affected by freezing: II. lipids and minerals - N. I. Mondy; Subhash Chandra (American Journal of Potato Research, 1979)

Quality of potato tubers as affected by freezing: I. texture, ascorbic acid and enzymatic discoloration - N. I. Mondy; Subhash Chandra (American Journal of Potato Research, 1979)